2015
DOI: 10.1103/physrevlett.115.120401
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Precision of Weak Measurements by Postselection Measurement

Abstract: Postselected weak measurement is a useful protocol to amplify weak physical effects. However, there has recently been controversy over whether it gives any advantage in precision. While it is now clear that retaining failed postselections can yield more Fisher information than discarding them, the advantage of postselection measurement itself still remains to be clarified. In this Letter, we address this problem by studying two widely used estimation strategies: averaging measurement results, and maximum likel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 69 publications
3
71
0
Order By: Relevance
“…Further, it has been shown that a computationally trivial estimator exists for time correlated noise and outperforms the weak-valueampli cation technique [16]. If one has chosen a suboptimal initial state |i ≠ |i * , then performing an optimal postselection f * | can lead to more (corrected) Fisher information than not performing the second measurement at all (case 1) [11] -otherwise, when |i * is chosen, the Fisher information of case 4 achieves the theoretical maximum and cannot be surpassed by any pre and postselected strategy, including an optimal one.…”
Section: Suboptimal Estimation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been shown that a computationally trivial estimator exists for time correlated noise and outperforms the weak-valueampli cation technique [16]. If one has chosen a suboptimal initial state |i ≠ |i * , then performing an optimal postselection f * | can lead to more (corrected) Fisher information than not performing the second measurement at all (case 1) [11] -otherwise, when |i * is chosen, the Fisher information of case 4 achieves the theoretical maximum and cannot be surpassed by any pre and postselected strategy, including an optimal one.…”
Section: Suboptimal Estimation Strategiesmentioning
confidence: 99%
“…[30][31][32]); for example with entanglement [33] or squeezing [11]. Both these e ects are known to unlock a genuine quantum advantage for certain metrological tasks, but at this point it is not clear whether combining them with weak values can indeed lead to anything greater than the sum of its parts.…”
Section: Combination With Other Quantum E Ectsmentioning
confidence: 99%
“…For a more complete overview of both the relevant theory and experiments, see the review article by Dressel et al [21]. There has been recent theoretical work examining the use of quantum optical resources in the meter degree of freedom which shows that it is possible for a postselected measurement to achieve higher sensitivity than non-postselected measurements [22,23]. However, the overwhelming majority of experimental work to date has used classical (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overwhelming majority of experimental work to date has used classical (i.e. coherent) states which can not improve over traditional schemes with postselection in ideal, shot-noise limited systems [23].…”
Section: Introductionmentioning
confidence: 99%
“…Since the Fisher information is proportional to the amount of the data and the postselection of the system discards a large portion of the measurement results, then the precision of the measurement may be lowered by the postselection. However, it was shown that the loss of Fisher information can be negligible when the initial state and the postselected state of the system are chosen properly [26,28,64,69,70], and that the signal-to-noise ratio (SNR) of postselected weak measurements can be made much higher than that of standard weak measurements by utilizing squeezed states for the probe [67].…”
Section: Introductionmentioning
confidence: 99%